Merriam-Webster's Essential Learner's English Dictionary (Espringfield, Massachusees, MEerriam Webster, 2010)
Read, write, and speak English with confidence - More than 54.000 words and phrases defined and explained with IPA pronunciations - More than 15.000 idioms, collocations, and commonly used phrases - Over 78.000 example sentences and phrases - Extensive usage labels, notes, and paragraphs - Perfect for students preparing for TOEFL and TOEIC tests TOEFL and TOEIC are registered trademarks of Educational Testing Service (ETS). This publication is not endorsed or approved by ETS. From America's Language Experts.
Using the dictionary -- Labels used in this dictionary -- Pronunciation symbols -- A dictionary of the english language -- Irregular verbs.
Perfect for studentes and teachers.
Resumen tomado del sitio web de la editorial
Genertal
Keywords: Inglés -- Diccionarios